Reply to “Comment on groundwater age, life expectancy and transit time distributions in advective–dispersive systems : 1. Generalized reservoir theory” by Timothy R. Ginn - Cornaton, Fabien; Perrochet, Pierre (My University, 2007)
We thank T.R. Ginn for his interest in our recently published article (1) on the subject of groundwater age modelling and reservoir theory. In his previous comment (2), T.R. Ginn expresses concern about some conceptual inconsistencies in the formulations presented in our work. We basically agree with the fundaments of his comments, and we wish to continue the discussion. (1) F. Cornaton and P. Perrochet, Groundwater age, life expectancy and transit time distributions in advective–dispersive systems: 1. Generalized reservoir theory, Adv Water Res 29 (2006), pp. 1267–1291, doi :10.1016/j.advwatres.2005.10.009 (2) Ginn TR. Comment on “Groundwater age, life expectancy and transit time distributions in advective–dispersive systems: 1. Generalized reservoir theory”, by F. Cornaton and P. Perrochet. Adv Water Res, in press, doi :10.1016/j.advwatres.2006.09.005.
Keywords: Groundwater age; Transient distributions; Probabilistic models; Deterministic models